Alice MacLeod, realist at last - Juby, Susan, 1969- (HarperTempest, 2006)
Sixteen-year-old Alice uses her screen-writing aspirations to help her get through a challenging period in her life after her boyfriend goes to Scotland, her mother is jailed for environmental activism, and her depressed father cannot get a job.